Respuesta :
Answer:
19y - 9
Step-by-step explanation:
We can use the acronym PEMDAS. First, we need to calculate -3(-4y+3) by distributing. This is -3 * (-4y) + (-3) * 3 = 12y - 9 so the expression becomes 12y - 9 + 7y. Next, we need to combine like terms. 12y and +7y are like terms since they both have y so combining them gives us 12y + 7y = 19y. -9 stays by itself since there are no other constants so the final answer is 19y - 9.
Answer:
Hey, it's really very easy to simplify .
I will write step by step.
Given:
= -3 (-4y + 3) +7y
Now, let's Distribute:
= (-3) (-4y) + (-3) (3) + 7y
= 12y + -9 + 7y
Now, Combine Like Terms:
= 12y + -9 + 7y
= (12y + 7y) + (-9)
= 19y + -9
Therefore, 19y + -9 is the answer.